The Economic Thought of Ibn Khaldun: A Review - Mimma Maripatul Uula (Islamic Economics and History, 2022)
This study aims to see the development of research "Ibnu Khaldun Economic Thought” around the world published by journals with that theme. This study used a qualitative method with a blibliometric analysis approach. The data used is secondary data with the theme "Ibnu Khaldun Economic Thought” which comes from the Dimension database. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the research development blibliometric map "Ibnu Khaldun Economic Thought" in this world. The results of the study found on bibliometrics author mapping author of the most published research on the themeIbnu Khaldun Economic Thought namely Akhmad Affandi, Siti Khatijah Ismail, Azlin Alisa Ahmad, Nor Syafinaz Md Safar, Amirul Hakim, Khadijah Isa, and Hairul Azlan Annuar. Then, the authors' organizations that contributed the most were Fatih University and University of Illinois Springfield, La Trobe University, Professor of Economic History, Universitat Autonoma de Barcelona, ​​Spain, and University College, Dublin, Ireland. Furthermore, based on the bibliometric keyword mapping, the most used words are khaldun, history, poverty, and corporate tax rate, and the trending keywords that frequently appear and are updated are Corporate Tax Rate, Urban Planning, Sustainable Development.